The complete mitochondrial genome of Nasutitermes tiantongensis Zhou et Xu, 1993 (Isoptera: Termitidae: Nasutitermitinae) - Kexin Qian; Haihong Chen; Jiaojuan Qian; Qijuan Gu; Dayu Zhang (Mitochondrial DNA. Part B. Resources, 2023)
Nasutitermes tiantongensis belongs to Nasutitermitinae and its mitochondrial genome was determined in this study. It consisted of 13 PCGs, 22 tRNAs, 2 rRNAs, and an A + T-rich control region, and its length was 15824 bp. The phylogenetic analysis suggested that the genus Nasutitermes was not monophyletic, and N. tiantongensis formed a sister group with Bultitermes laticephalus. The mitochondrial genome of N. tiantongensis provides a resource for evolutionary analysis within Nasutitermitinae.